The greatest cattle drive - Wellman, Paul Iselin; Bjorklund, Lorence F. (Boston : Houghton Mifflin Company, 1964)
An account of how, in 1866, "Nelson Story, starting from Texas with a herd of 1000 cattle and a crew of 24 men, braved stampedes, flooded rivers, enraged Indian tribes, waterless deserts and mountain blizzards to bring the cattle over unmapped trails to the Montana gold camps".
Includes index.
Bibliography: p.[181]
Keywords: Story, Nelson; Story, Nelson; Story, Nelson -- Juvenile literature; Cattle trade; Cattle trade -- West (U.S.) -- History -- 19th century -- Juvenile literature; Cattle; Cowboys; Cowboys -- West (U.S.) -- History -- Juvenile literature; Cowhands; West (U.S.) -- History; West (U.S.) -- History -- 1848-1950.; West (U.S.) -- History -- 1848-1950 -- Juvenile literature